Control del minador de la hoja Phyllocnistis citrella en el cultivo de limón Citrus limon - Carbo Mosquera, José Javier (2024)
The development of the case study in which the objective was to analyze the control of the leaf miner P. citrella in the lemon crop C. limon. Regarding the methodology, it was developed as non-experimental research of a bibliographic nature, where updated and relevant information was collected from scientific articles, websites and virtual libraries that provide information that will allow the development of this research. In results, the leaf miner, a common pest in lemon crops C. limon, can cause considerable damage to plants, mainly affecting the leaves. The larvae of this insect mine the leaves by feeding on the internal tissue, creating tunnels, serpentines that weaken the leaf structure, this process, known as "mining", reduce the photosynthetic capacity of the leaves, negatively affecting the growth and development of the plant. In conclusion, the implementation of integrated strategies is essential to successfully manage this pest, the combination of preventive methods, such as constant monitoring and the application of pheromone traps, together with the selective use of insecticides, when necessary, is positioned as an approach, balanced and sustainable.